In silico and Molecular Docking Studies of Black Pepper Phyto-constituents against EmrD Efflux Pump of E. coli - Dongre, Prerana; Bhambar, Rajendra; Polshettiwar, Satish (Indian Journal of Pharmaceutical Education and Research, 2022)
Multidrug resistance (MDR) bacterial infection is the next pandemic waiting behind the COVID-19 with annual mortality rate 700000 worldwide. Among the MDR bacteria, Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterococcus faecium and Enterococcus faecalis are showing average resistance of 50 to 80% to ampicillin, amoxicillin, third-generation cephalosporin’s and fluoroquinolone and even to combinations antibiotics such as amoxicillin-clavulanic acid. To make the antibiotic resistance issue worst, pharmaceutical industry is reluctant to invest in research and development of new antibiotic typically due to low returns on investment. Accordingly, use of combination of two or more antibiotics or use of the antibiotic adjuvants are only available ways in combatting the ever growing Multidrug resistance (MDR) in bacteria. The present paper is designed to analyze the synergistic potential of black pepper phyto-constituents as the amoxicillin adjuvants in comparison with isolated piperine against the MDR E. coli. using in-silico molecular docking. The result indicates that binding energy (Kcal/mol) and torsion free energy (Kcal/mol) of piperine (-6.23, +0.89), beta caryophyllene (-6.36, +0.00), beta selinene (-6.93, +0.30), beta-Thujene (-5.42, +0.30) is less for the emrD efflux pump as compared to amoxicillin (-5.85, +2.93) respectively indicating strong inhibition for EmrD of MDR E-coli than amoxicillin. The results are also indicating that black pepper extract containing all aforementioned phyto-constituents has synergistic effect in comparison with isolated piperine against the MDR E. coli. ADMET of these phyto-constituents also indicates their safety profile in combination with amoxicillin.
Keywords: Multidrug resistance (MDR); Piperine; In silico molecular docking; Efflux; pump; E. coli; Black pepper; Amoxicillin